Behaviour of thick marine deposits subjected to vacuum combined with surcharge preloading. Issue 10 (3rd October 2021) - Zhang, Dikang; Fu, Hongtao; Wang, Jun; Zhu, Dongqi; Hu, Xiuqing; Du, Yunguo; Gou, Changfei; Wang, Chaoliang; Li, Mingfeng; Wu, Hai
Abstract: This paper presents a case study on the improvement of thick marine deposits. A new method that combines vacuum pressure and surcharge load with no need for a sand cushion is proposed and evaluated. The main features of this method are as follows: (1) each integrated prefabricated vertical drain (PVD) is connected directly to a branch pipe, which is in turn connected to a main pipe with a T-shaped connector, and (2) a less expensive hill-skill soil layer is used to replace the sand cushion. After improving the soil by using this method, the total ground settlement, the lateral deformation and the undrained shear strength were all greater for a 20-m PVD than for a 15-m PVD. The average degrees of consolidation achieved were both greater than 80%. This method could provide design criteria for reclaimed land in other projects.